2019
DOI: 10.1111/jsap.13059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of dogs with presumed primary renal lymphoma

Abstract: Objectives To characterise the presentation, clinicopathologic data and outcome of 29 dogs with presumed primary renal lymphoma. Materials and Methods Retrospective analysis of medical records of dogs with suspected primary renal lymphoma from 11 institutions. Results All dogs were substage b, and lethargy and gastrointestinal signs were common presenting complaints, as were azotaemia (n=25; 86%) and erythrocytosis (n=15; 51%) on biochemical testing. Ultrasonography typically revealed bilateral renal lesions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…6 In the present case, there was a slight increase of EPO, most likely due to the presence of the renal neoplasia. 2,6 For decades, abdominal ultrasound has been one of the main diagnostic tools to evaluate the kidneys when abnormalities in the renal architecture are suspected. Several studies have reported that the sonographic findings in dogs with renal lymphoma include renomegaly, hypoechoic lesions, pyelectasia and bilateral involvement; however, in our patient the sonographic appearance was that of a heterogeneous masstype lesion that distorted the normal renal morphology, rather than hypoechoic nodules.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 In the present case, there was a slight increase of EPO, most likely due to the presence of the renal neoplasia. 2,6 For decades, abdominal ultrasound has been one of the main diagnostic tools to evaluate the kidneys when abnormalities in the renal architecture are suspected. Several studies have reported that the sonographic findings in dogs with renal lymphoma include renomegaly, hypoechoic lesions, pyelectasia and bilateral involvement; however, in our patient the sonographic appearance was that of a heterogeneous masstype lesion that distorted the normal renal morphology, rather than hypoechoic nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the case described by Froment and Gara‐Boivin in 2015, it was very likely that the erythrocytosis observed in our patient was an inappropriate secondary type, since, although arterial blood gas analysis was not performed, the patient presented a normal cardiovascular examination, not supporting systemic hypoxia. Secondary polycythaemia due to inappropriately elevated EPO is an infrequent paraneoplastic syndrome associated with infiltrative renal neoplasia 2, 6 . The increase in EPO production has been explained by two possible mechanisms, either the neoplastic cells are the ones that generate the ectopic production of EPO or an EPO‐like substance, or the neoplastic infiltration produces compression of the renal tissue and vascular supply causing local renal hypoxia that would originate a physiologically‐induced EPO production from hypoxic renal cells 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations